The Necessity of Legal Protection for Geographical Indications within a Sui Generis Framework - Rohmat, Rohmat; Wei, David Chuah Cee (Faculty of Law, Universitas Pattimura, 2025)
Introduction: Legal and political activities are inherently interconnected in the pursuit of creating fair and just products for society. This relationship exists because the process of lawmaking, as reflected in statutory regulations, is inseparable from political activity. From an intellectual property perspective, geographical elements can serve both as trademarks and as indicators of a product's regional origin. This dual function creates regulatory overlap between trademark laws and geographical indication protections.Purposes of the Research: This research was conducted to assess the urgency of establishing a sui generis law for geographical indications.Methods of the Research: This research is normatively juridical with a statutory approach and a conceptual approach.Results Main Findings of the Research: The TRIPs Agreement emphasizes that Geographical Indications (GIs) constitute a distinct intellectual property regime, separate from trademarks. The legal policy established in Law Number 20 of 2016 aims to protect both moral and economic rights while preventing violations of communally owned GIs. Substantively, sui generis protection streamlines the registration process for GIs and enhances public participation in their registration and protection, aligning with Indonesia's legal and political direction on GI regulation.